Game of Zones: The Political Economy of Conservation Areas - Gabriel M. Ahlfeldt; Kristoffer Möller; Sevrin Waights; Nicolai Wendland (Center for Economic Studies and ifo Institute (CESifo), 2014)
Provided there are positive external benefits attached to the historic character of buildings, owners of properties in designated conservation areas benefit from a reduction in uncertainty regarding the future of their area. At the same time, the restrictions put in place to ensure the preservation of the historic character limit the degree to which properties can be altered and thus impose a cost to their owners. We test a simple theory of the designation process in which we postulate that the level of designation is chosen to comply with interests of local homeowners. The implication of the model is that a) an increase in preferences for historic character should increase the likelihood of a designation, and b) new designations at the margin should not be associated with significant house price capitalization effects. Our empirical results are in line with these predictions.
Keywords: H23; H31; R40; R58; 330; designation; difference-in-difference; RDD-DD; England; gentrification; heritage; property value